Releasing the tether: Weight normalization following corrective spinal fusion in cerebral palsy. (22nd June 2018) - DeFrancesco, Christopher J; Miller, Daniel J; Cahill, Patrick J; Spiegel, David A; Flynn, John M; Baldwin, Keith D
Purpose: Feeding difficulties are common among patients with cerebral palsy (CP) and neuromuscular (NM) scoliosis. We theorize that posterior spinal fusion (PSF) reduces intra-abdominal pressure, resulting in improved feeding and subsequent weight gain. We hypothesized that, among nonambulatory patients with CP and NM scoliosis, we would observe significant gain in weight following PSF. Methods: Fifty subjects with nonambulatory CP who underwent PSF for NM scoliosis were included. Age and weight were recorded for the preoperative year; on the day of surgery; and at 6-month, 1-year, and 2-year follow-up. Weights were converted to weight percentiles using CP-specific growth charts. The weight percentile distributions were compared between time points using descriptive statistics as well as regression analysis. Results: The average change in weight from the day of surgery to 2-year follow-up was +3.4 percentiles. Patients who started out under the 50th percentile gained an average of 17.3 percentiles in the first year after PSF ( p = 0.009). Regression analysis showed that patients with baseline weight <50th percentile tended to gain in weight percentile over the first postoperative year ( β = 1.990, p = 0.001). No trend was present among this group prior to surgery ( p = 0.692) or during the second postoperative year ( p = 0.945). No trends were noted prior to or after surgery for patients with baseline weights ≥50th percentile. No significant association was observed between curve severity (measured by preoperative Cobb angle) and weight change. Conclusions: This series is the first to document significant weight gain after PSF for NM scoliosis, supporting the theory that spinal correction improves digestive function. Level of Evidence: Prognostic level II.